Green low-emission high-viscosity modified asphalt and preparation process thereof

By introducing environmentally friendly high-viscosity additives and odor-cleaning ingredients into the asphalt, the composition and preparation process of asphalt are optimized, and the problem of difficult to reduce the emission of harmful substances in asphalt flue gas in the prior art is solved, and the asphalt materials with high viscosity and durability are achieved, meeting the environmental protection and performance requirements of modern road projects.

CN119570276AInactive Publication Date: 2025-03-07SHANDONG DAOXING HIGHWAY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510029385.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the emission of harmful substances in asphalt flue gas, while maintaining the high viscosity and durability of asphalt, which cannot meet the dual requirements of environmental protection and performance of modern road projects.

Method used

By introducing environmentally friendly high-viscosity additives and odor-cleaning ingredients, the composition and preparation process of asphalt are optimized, and the emission of harmful substances in asphalt flue gas is significantly reduced. The environmentally friendly high viscosity additive consists of natural resins and bio-based polymers. The odor clean component is a surface-modified porous adsorption material, and the stabilizer is an organic silicon compound.

Benefits of technology

It significantly reduces the emission of harmful substances in asphalt flue gas, improves the adhesion and anti-aging properties of asphalt, and meets the dual requirements of environmental protection and performance of modern road projects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Green low-emission high-viscosity modified asphalt relates to the technical field of road materials, and is prepared from the following raw materials in parts by weight: 100 parts of matrix asphalt, 3 to 8 parts of environment-friendly high-viscosity additive, 1 to 3 parts of odor removal component and 0.5 to 2 parts of stabilizer. The environment-friendly high-viscosity additive is composed of natural resin and a bio-based polymer, the odor removal component is a surface-modified porous adsorption material, and the stabilizer is an organosilicon compound. By optimizing the preparation process and improving the construction method, the emission of harmful substances in asphalt flue gas is remarkably reduced, meanwhile, the high viscosity and durability of asphalt are kept, and the environmental protection and performance requirements of modern road engineering are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of road materials, and specifically relates to green, low-emission, high-viscosity modified asphalt and a preparation process thereof. Background Art

[0002] In the field of road engineering, asphalt materials are widely used in road paving and maintenance due to their excellent adhesion, waterproofness and durability. However, traditional asphalt produces a large amount of harmful smoke during the construction process, including carcinogens such as polycyclic aromatic hydrocarbons (PAHs) and benzo[a]pyrene, which cause serious harm to construction workers and the environment. With the increasingly stringent environmental regulations, the development of low-emission, high-performance green asphalt materials has become an important research direction in the industry. In the existing technology, the performance of asphalt is improved by adding polymer modifiers (such as SBS, SBR) or nanomaterials (such as nano-SiO2, nano-TiO2), but these modifiers have limited effects in reducing smoke emissions and may introduce new environmental problems.

[0003] For example, Chinese patent CN104559263A discloses a nano / polymer composite modified asphalt material. Although it improves the high temperature stability and low temperature crack resistance of asphalt to a certain extent, the high surface energy of the nanomaterial easily leads to agglomeration, affecting its uniform dispersion in asphalt, and fails to effectively solve the emission problem of harmful substances in asphalt fume. Therefore, there is an urgent need for a green modified asphalt technology that can maintain the excellent performance of asphalt and significantly reduce the emission of harmful substances, so as to meet the dual requirements of environmental protection and performance of modern road engineering. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a solution for green, low-emission, high-viscosity modified asphalt.

[0005] The technical solution adopted by the present invention to solve its technical problem is: a green, low-emission, high-viscosity modified asphalt, characterized in that its raw material weight composition includes: 100 parts of base asphalt, 3-8 parts of environmentally friendly high-viscosity additives, 1-3 parts of odor-free ingredients, and 0.5-2 parts of stabilizer.

[0006] The present invention optimizes the composition and preparation process of asphalt by introducing environmentally friendly high-viscosity additives and odor-free components, thereby significantly reducing the emission of harmful substances in asphalt fume, while maintaining the high viscosity and durability of the asphalt.

[0007] Environmentally friendly high-viscosity additives are composed of natural resins and bio-based polymers in a specific proportion, which can effectively improve the adhesion and anti-aging properties of asphalt. The odor-free component is a surface-modified porous adsorption material that can adsorb harmful substances such as polycyclic aromatic hydrocarbons (PAHs) and benzo[a]pyrene in asphalt smoke. The stabilizer is an organosilicon compound used to improve the dispersion and compatibility of the additive in asphalt.

[0008] Preferably, in the composition of the green, low-emission, high-viscosity modified asphalt, the environmentally friendly high-viscosity additive is composed of rosin resin and polylactic acid in a mass ratio of 1.6 to 2.3: 1. The rosin resin provides excellent adhesion, and the polylactic acid enhances the anti-aging performance of asphalt.

[0009] Preferably, the preparation process of the above-mentioned environmentally friendly high-viscosity additive comprises the following steps: 1) Weigh rosin resin and polylactic acid according to mass ratio; 2) Preheat the rosin resin and polylactic acid separately. The preheating temperature of the rosin resin is 130℃~140℃, and the preheating temperature of the polylactic acid is 120~130℃; the preheating time is 10min~15min to ensure that the two can be fully melted during the mixing process to improve the uniformity of the final product; 3) Mix the preheated rosin resin and polylactic acid at 135℃~145℃ for 20min~30min, and the speed of the mixer is 600 rpm~800 rpm to ensure that the two raw materials can be fully mixed at high temperature to form a stable homogeneous system; cool and crush. The temperature of the cooling mold is 20℃~30℃, and the cooling time is 30min~40min. During the cooling process, the mixture is quickly cooled to room temperature through the cooling water circulation system to prevent the additive from stratification or crystallization during the cooling process, ensuring the uniformity and stability of the final product. The completely cooled high-viscosity additive is crushed, and the particle size after crushing is controlled to be 0.1~0.5 mm. The crushed additive is sieved through a sifter to ensure a uniform particle size distribution to improve its dispersibility and fluidity in the application.

[0010] Preferably, in the composition of the green, low-emission, high-viscosity modified asphalt, the odor-free component is surface-modified activated carbon, with a specific surface area of ​​800m² / g~1200m² / g and a pore size distribution of 2nm~5nm, which can efficiently adsorb polycyclic aromatic hydrocarbons and benzo[a]pyrene in asphalt fume.

[0011] Preferably, the preparation process of the above surface modified activated carbon is: a) preparing a modified liquid with a sulfur-containing compound, a surfactant and deionized water, wherein the mass concentration of the sulfur-containing compound in the modified liquid is 0.1% to 5%, the mass concentration of the surfactant is 0.05% to 2%, and the balance is deionized water; b) Add the activated carbon matrix into the modified liquid and perform an impregnation treatment for 1h~6h to allow the modifier and additive to fully penetrate the surface of the activated carbon; c) Take out the activated carbon substrate after impregnation treatment, dry it, and then heat treat it at 300℃~600℃ for 1h~3h to allow the modified layer to form a stable structure on the surface of the activated carbon, and then cool and crush it.

[0012] The modified layer is composed of sulfur-containing compounds and surfactants. The sulfur-containing compounds react chemically with the functional groups on the surface of the activated carbon during the heat treatment process to form stable chemical bonds, thereby forming a uniform modified layer on the surface of the activated carbon. The surfactant promotes the uniform distribution of the sulfur-containing compounds on the surface of the activated carbon during the modification process, and decomposes into small molecules or volatilizes during the heat treatment process, which will not affect the structure of the modified layer.

[0013] By controlling the concentration of the modifying liquid, the immersion time and the heat treatment temperature, the thickness of the modified layer can be precisely controlled. The thickness of the modified layer is crucial to the performance of the activated carbon. A modified layer that is too thick will affect the pore structure of the activated carbon, and a modified layer that is too thin will not effectively improve the surface properties of the activated carbon. The present invention precisely controls these parameters so that the thickness of the modified layer is between 1nm and 50nm, preferably between 5nm and 20nm, thereby significantly improving its surface properties while ensuring the pore structure of the activated carbon.

[0014] The introduction of surfactants makes the distribution of sulfur-containing compounds on the surface of activated carbon more uniform, avoiding the situation of local excessive thickness or thinness. The role of surfactants is to reduce the surface tension of the modified liquid, making it easier for the modified liquid to penetrate into the micropores of activated carbon, thereby achieving uniform distribution of the modifier on the surface of activated carbon.

[0015] During the heat treatment process, the sulfur-containing compound reacts chemically with the functional groups on the surface of the activated carbon to form stable chemical bonds. The surfactant decomposes into small molecules or volatilizes during the heat treatment process, which will not affect the structure of the modified layer. The control of the heat treatment temperature and time is key, and too high or too low temperature will affect the formation of the modified layer. The present invention ensures that the modified layer forms a stable structure on the surface of the activated carbon by controlling the heat treatment temperature at 300°C to 600°C and the heat treatment time at 1h to 3h, thereby improving the modification effect of the activated carbon.

[0016] Preferably, in the above-mentioned process for preparing surface-modified activated carbon, the sulfur-containing compound in step a) is a dibenzothiophene organic sulfur compound, and the surfactant is sodium dodecyl sulfate or oxyethylated octylphenol.

[0017] More preferably, the dibenzothiophene organic sulfur compound is dibenzothiophene (DBT), 4-methyl-dibenzothiophene, 4,6-dimethyl-dibenzothiophene, 3,7-dimethyl-dibenzothiophene or 2,8-dimethyl-dibenzothiophene.

[0018] Preferably, in the above-mentioned process for preparing surface-modified activated carbon, the mass concentration of the sulfur-containing compound in the modified liquid in step a) is 1% to 2.5%, and the mass concentration of the surfactant is 0.5% to 1.5%. More preferably, the mass concentration of the sulfur-containing compound in the modified liquid is 1.5%, and the mass concentration of the surfactant is 1.0%.

[0019] Preferably, in the above-mentioned process for preparing surface-modified activated carbon, the impregnation time in step b) is 2 h to 4 h.

[0020] Preferably, in the above-mentioned process for preparing surface-modified activated carbon, the drying temperature in step c) is 80° C. to 120° C., and the drying time is 6 h to 12 h, so as to remove excess modification liquid.

[0021] Preferably, in the composition of the green, low-emission, high-viscosity modified asphalt, the stabilizer is methyl silicone oil, methyl vinyl silicone oil, methyl ethoxy silicone oil or hydroxy silicone oil. More preferably, it is methyl silicone oil, and the addition amount is 0.5 to 1 part, which is used to improve the dispersibility and compatibility of environmentally friendly high-viscosity additives and odor-free components in asphalt.

[0022] Through the implementation of the above technical solutions, the present invention not only significantly reduces the emission of harmful substances in asphalt fume, but also maintains the high viscosity and durability of asphalt, meeting the dual requirements of modern road engineering for environmental protection and performance.

[0023] A process for preparing the above-mentioned green, low-emission, high-viscosity modified asphalt comprises the following steps: 1) After heating the base asphalt to 160℃~180℃, add the environmentally friendly high-viscosity additive, odor-free component and stabilizer in sequence, and stir in a high-speed shear mixer at a speed of 3000r / min~5000r / min for 30min~60min to ensure that all components are evenly dispersed; 2) Keep the mixture at 150℃~160℃ for 2h~4h to allow the additive to fully react with the asphalt to obtain green, low-emission, high-viscosity modified asphalt.

[0024] Preferably, the base asphalt is petroleum asphalt with a needle penetration of 60-80 and a softening point of 45°C-50°C, ensuring that the initial performance of the modified asphalt meets the requirements of road engineering.

[0025] An improved construction method, characterized in that: during the asphalt paving process, low-temperature paving technology is used to control the construction temperature at 130°C to 150°C, thereby reducing the generation of asphalt smoke and improving the asphalt paving efficiency. At the same time, a smoke collection device is set up at the construction site to further purify the emitted smoke through an activated carbon filtration system.

[0026] Furthermore, the activated carbon filtration system of the flue gas collection device adopts a multi-layer structure, each layer of activated carbon is 10 cm thick, and the flue gas passing speed is 0.5 m / s, ensuring efficient removal of residual harmful substances in the flue gas.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: the green, low-emission, high-viscosity modified asphalt of the present invention significantly reduces the emission of harmful substances in asphalt fume by introducing environmentally friendly high-viscosity additives and odor-free components, while improving the adhesion and anti-aging properties of asphalt. The environmentally friendly high-viscosity additive is composed of rosin resin and polylactic acid. The rosin resin provides excellent adhesion, enhances the skid resistance and water damage resistance of the road surface, while the polylactic acid enhances the anti-aging properties of asphalt and prolongs the service life. The stabilizer is an organosilicon compound, which improves the dispersibility and compatibility of the additive in the asphalt and ensures the long-term stability of the modified asphalt. The preparation process is simple and controllable, and the quality stability and performance consistency of the modified asphalt can be ensured through the steps of heating, mixing, heat preservation and standing. This modified asphalt not only meets the dual requirements of modern road engineering for environmental protection and performance, but also has excellent adhesion, anti-aging properties and stability. DETAILED DESCRIPTION

[0028] The present invention provides a specific implementation scheme for realizing the preparation and application of green, low-emission, high-viscosity modified asphalt. First, base asphalt, environmentally friendly high-viscosity additives, odor-free components and stabilizers are prepared according to the weight of raw materials. The base asphalt uses petroleum asphalt with a needle penetration of 60 to 80 and a softening point of 45°C to 50°C to ensure that the initial performance of the modified asphalt meets the requirements of road engineering. The environmentally friendly high-viscosity additive is composed of rosin resin and polylactic acid in a mass ratio of 1.6 to 2.3:1, the rosin resin provides excellent adhesion, and the polylactic acid enhances the anti-aging performance of asphalt. The odor-free component is a specific surface-modified activated carbon with a specific surface area of ​​800m² / g to 1200m² / g and a pore size distribution of 2nm to 5nm, which can efficiently adsorb polycyclic aromatic hydrocarbons and benzo[a]pyrene in asphalt fume. The stabilizer is preferably methyl silicone oil, which is added in an amount of 0.5 to 1 part, and is used to improve the dispersibility and compatibility of the environmentally friendly high-viscosity additive and the odor-free component in asphalt.

[0029] During the preparation process, the base asphalt is heated to 160℃~180℃, and environmentally friendly high-viscosity additives, odor-free ingredients and stabilizers are added in sequence, and stirred in a high-speed shear mixer at a speed of 3000~5000 rpm for 30~60 minutes to ensure that the components are evenly dispersed. The mixture is then kept at 150℃~160℃ for 2h~4h to allow the additives to fully react with the asphalt, and finally a green, low-emission, high-viscosity modified asphalt is obtained.

[0030] During the construction process, low-temperature paving technology is used to control the construction temperature at 130℃~150℃ to reduce the generation of asphalt fume. At the same time, a fume collection device is set up at the construction site to further purify the emitted fume through an activated carbon filtration system. The activated carbon filtration system adopts a multi-layer structure, with each layer of activated carbon being 10 cm thick and the fume passing speed being 0.5m / s, ensuring the efficient removal of harmful substances in the fume.

[0031] In order to verify the feasibility and effectiveness of the present invention, multiple experiments were conducted. The experimental results show that the green, low-emission, high-viscosity modified asphalt prepared by the present invention has achieved the expected performance goals and has high production efficiency and stability.

[0032] Preparation of environmentally friendly high viscosity additive A 1) Weigh rosin resin and polylactic acid at a mass ratio of 2.0:1; 2) Preheat the rosin resin and polylactic acid separately, the preheating temperature of the rosin resin is 135°C, the preheating temperature of the polylactic acid is 125°C, and the preheating time is 12 minutes; 3) Mix the preheated rosin resin and polylactic acid at 140°C for 25 minutes; cool and crush to obtain.

[0033] Preparation of environmentally friendly high viscosity additive B 1) Weigh rosin resin and polylactic acid in a mass ratio of 1.6:1; 2) Preheat the rosin resin and polylactic acid separately, the preheating temperature of the rosin resin is 130°C, the preheating temperature of the polylactic acid is 120°C, and the preheating time is 10 minutes; 3) Mix the preheated rosin resin and polylactic acid at 135°C for 30 minutes; cool and crush to obtain.

[0034] Preparation of environmentally friendly high viscosity additive C 1) Weigh rosin resin and polylactic acid in a mass ratio of 2.3:1; 2) Preheat the rosin resin and polylactic acid separately, the preheating temperature of the rosin resin is 140°C, the preheating temperature of the polylactic acid is 130°C, and the preheating time is 15 minutes; 3) Mix the preheated rosin resin and polylactic acid at 145°C for 20 minutes; cool and crush to obtain.

[0035] Preparation of surface modified activated carbon A a) preparing a modification solution with dibenzothiophene, sodium dodecyl sulfate and deionized water, wherein the mass concentration of dibenzothiophene in the modification solution is 1.5%, the mass concentration of sodium dodecyl sulfate is 1.0%, and the balance is deionized water; b) adding the activated carbon substrate into the modified liquid for impregnation treatment for 3 hours; c) The activated carbon substrate after impregnation treatment was taken out, dried at 100°C for 9 hours, and then heat treated at 450°C for 2 hours to obtain surface-modified activated carbon with a specific surface area of ​​1000m² / g and a pore size distribution of 3nm.

[0036] Preparation of surface modified activated carbon B a) preparing a modification solution with dibenzothiophene, sodium dodecyl sulfate and deionized water, wherein the mass concentration of dibenzothiophene in the modification solution is 1%, the mass concentration of sodium dodecyl sulfate is 0.5%, and the balance is deionized water; b) adding the activated carbon substrate into the modified liquid for impregnation treatment for 2 hours; c) The activated carbon substrate after impregnation treatment was taken out, dried at 110°C for 8.5h, and then heat treated at 400°C for 2.5h to obtain surface-modified activated carbon with a specific surface area of ​​1080m² / g and a pore size distribution of 2.9nm.

[0037] Preparation of surface modified activated carbon C a) preparing a modification solution with dibenzothiophene, sodium dodecyl sulfate and deionized water, wherein the mass concentration of dibenzothiophene in the modification solution is 2.5%, the mass concentration of sodium dodecyl sulfate is 1.5%, and the balance is deionized water; b) adding the activated carbon substrate into the modified liquid for impregnation treatment for 4 hours; c) The activated carbon substrate after impregnation treatment was taken out, dried at 95°C for 9.5h, and then heat treated at 500°C for 1.5h to obtain surface-modified activated carbon with a specific surface area of ​​930m² / g and a pore size distribution of 3.3nm.

[0038] Preparation of surface modified activated carbon D a) preparing a modification liquid with 4-methyl-dibenzothiophene, oxyethylated octylphenol and deionized water, wherein the mass concentration of the sulfur-containing compound in the modification liquid is 5%, the mass concentration of the surfactant is 2%, and the balance is deionized water; b) adding the activated carbon substrate into the modified liquid for impregnation treatment for 1 hour; c) The activated carbon substrate after impregnation treatment was taken out, dried at 80°C for 12 hours, and then heat treated at 300°C for 3 hours to obtain surface-modified activated carbon with a specific surface area of ​​800m² / g and a pore size distribution of 2nm.

[0039] Preparation of surface modified activated carbon E a) preparing a modification liquid with 4-methyl-dibenzothiophene, sodium dodecyl sulfate and deionized water, wherein the mass concentration of the sulfur-containing compound in the modification liquid is 0.1%, the mass concentration of the surfactant is 0.05%, and the balance is deionized water; b) adding the activated carbon substrate into the modified liquid for impregnation treatment for 6 hours; c) The activated carbon substrate after impregnation treatment was taken out, dried at 120°C for 6 hours, and then heat treated at 600°C for 1 hour to obtain surface-modified activated carbon with a specific surface area of ​​1200m² / g and a pore size distribution of 5nm. Example 1

[0040] In this embodiment, there are 100 parts of base asphalt, 5 parts of environmentally friendly high-viscosity additive A, 2 parts of surface-modified activated carbon A, and 1 part of methyl silicone oil. The base asphalt is heated to 170°C, and the environmentally friendly high-viscosity additive, surface-modified activated carbon and stabilizer are added in sequence, and stirred at a speed of 4000 rpm in a high-speed shear mixer for 45 minutes to ensure that the components are evenly dispersed. The mixture is then kept at 155°C for 3 hours to allow the additive to fully react with the asphalt, and finally a green, low-emission, high-viscosity modified asphalt is obtained. After testing, the viscosity of the asphalt (25°C) is 7850 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 61%. Example 2

[0041] The basic ratio and preparation process are the same as those in Example 1, except that the surface-modified activated carbon A is replaced by an equal amount of ordinary activated carbon. According to the test, the viscosity of the asphalt (25°C) is 7670 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 31%. Example 3

[0042] The basic ratio and preparation process are the same as those in Example 1, except that the environmentally friendly high-viscosity additive A is replaced by the environmentally friendly high-viscosity additive B; and the surface-modified activated carbon A is replaced by the surface-modified activated carbon B. After testing, the viscosity of the asphalt (25°C) is 7460 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 56%. Example 4

[0043] The basic ratio and preparation process are the same as those in Example 1, except that the environmentally friendly high-viscosity additive A is replaced by the environmentally friendly high-viscosity additive C; and the surface-modified activated carbon A is replaced by the surface-modified activated carbon C. After testing, the viscosity of the asphalt (25°C) is 7520 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 57%. Example 5

[0044] The basic ratio and preparation process are the same as those in Example 1, except that the environmentally friendly high-viscosity additive A is replaced by the environmentally friendly high-viscosity additive B; and the surface-modified activated carbon A is replaced by the surface-modified activated carbon D. After testing, the viscosity of the asphalt (25°C) is 7230 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 53%. Example 6

[0045] The basic ratio and preparation process are the same as those in Example 1, except that the environmentally friendly high-viscosity additive A is replaced by the environmentally friendly high-viscosity additive C; and the surface-modified activated carbon A is replaced by the surface-modified activated carbon E. After testing, the viscosity of the asphalt (25°C) is 7180 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 51%. Example 7

[0046] In this embodiment, there are 100 parts of base asphalt, 8 parts of environmentally friendly high-viscosity additive A, 1 part of surface-modified activated carbon A, and 0.5 parts of methyl silicone oil. The base asphalt is heated to 160°C, and the environmentally friendly high-viscosity additive, surface-modified activated carbon and stabilizer are added in sequence, and stirred at a speed of 3000 rpm in a high-speed shear mixer for 60 minutes to ensure that the components are evenly dispersed. The mixture is then kept at 160°C for 2 hours to allow the additive to fully react with the asphalt, and finally a green, low-emission, high-viscosity modified asphalt is obtained. After testing, the viscosity of the asphalt (25°C) is 6800 mPa·s, and the emission of benzo[a]pyrene in the flue gas is reduced by 48%. Example 8

[0047] In this embodiment, there are 100 parts of base asphalt, 3 parts of environmentally friendly high-viscosity additive A, 3 parts of surface-modified activated carbon A, and 2 parts of methyl silicone oil. The base asphalt is heated to 180°C, and the environmentally friendly high-viscosity additive, surface-modified activated carbon and stabilizer are added in sequence, and stirred at a speed of 5000 rpm in a high-speed shear mixer for 30 minutes to ensure that the components are evenly dispersed. The mixture is then kept at 150°C for 4 hours to allow the additive to fully react with the asphalt, and finally a green, low-emission, high-viscosity modified asphalt is obtained. After testing, the viscosity of the asphalt (25°C) is 6200 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 52%.

[0048] Comparative Example 1 The basic ratio and preparation process are the same as those in Example 1, except that no environmentally friendly high-viscosity additive A is added. After testing, the viscosity of the asphalt (25°C) is 4112 mPa·s, and the emission of polycyclic aromatic hydrocarbons in the flue gas is reduced by 47%.

[0049] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A green, low-emission, high-viscosity modified asphalt, characterized in that: The raw materials include, by weight, 100 parts of base asphalt, 3-8 parts of environmentally friendly high-viscosity additives, 1-3 parts of odor-free ingredients, and 0.5-2 parts of stabilizers.

2. A green, low-emission, high-viscosity modified asphalt according to claim 1, characterized in that: The environmentally friendly high-viscosity additive is composed of rosin resin and polylactic acid in a mass ratio of 1.6-2.3:

1.

3. A green, low-emission, high-viscosity modified asphalt according to claim 2, characterized in that: The preparation process of the environmentally friendly high-viscosity additive comprises the following steps: 1) Weigh rosin resin and polylactic acid according to mass ratio; 2) Preheat the rosin resin and polylactic acid separately. The preheating temperature of the rosin resin is 130℃~140℃, the preheating temperature of the polylactic acid is 120℃~130℃, and the preheating time is 10min~15min; 3) Mix the preheated rosin resin and polylactic acid at 135℃~145℃ for 20min~30min; cool and crush to obtain.

4. The green, low-emission, high-viscosity modified asphalt according to claim 1, characterized in that: The deodorizing component is surface-modified activated carbon, the specific surface area of ​​which is 800m² / g~1200m² / g and the pore size distribution is 2nm~5nm.

5. A green, low-emission, high-viscosity modified asphalt according to claim 4, characterized in that: The preparation process of the surface modified activated carbon is: a) preparing a modified liquid with a sulfur-containing compound, a surfactant and deionized water, wherein the mass concentration of the sulfur-containing compound in the modified liquid is 0.1% to 5%, the mass concentration of the surfactant is 0.05% to 2%, and the balance is deionized water; b) Adding the activated carbon matrix into the modified liquid for impregnation treatment, the impregnation time is 1h~6h; c) Take out the activated carbon substrate after impregnation treatment, dry it, and then heat treat it at 300℃~600℃ for 1h~3h.

6. The green, low-emission, high-viscosity modified asphalt according to claim 5, characterized in that: The sulfur-containing compound in step a) is a dibenzothiophene organic sulfur compound, and the surfactant is sodium dodecyl sulfate or oxyethylated octylphenol.

7. The green, low-emission, high-viscosity modified asphalt according to claim 6, characterized in that: In step a), the mass concentration of the sulfur-containing compound in the modified liquid is 1% to 2.5%, and the mass concentration of the surfactant is 0.5% to 1.5%.

8. The green, low-emission, high-viscosity modified asphalt according to claim 6, characterized in that: The immersion time in step b) is 2h~4h.

9. The green, low-emission, high-viscosity modified asphalt according to claim 1, characterized in that: The stabilizer is methyl silicone oil.

10. A process for preparing the green, low-emission, high-viscosity modified asphalt according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) After heating the base asphalt to 160℃~180℃, add the environmentally friendly high-viscosity additive, odor-free component and stabilizer in sequence, and stir in a high-speed shear mixer at a speed of 3000r / min~5000r / min for 30min~60min; 2) Keep the mixture at 150℃~160℃ for 2h~4h to obtain green, low-emission and high-viscosity modified asphalt.

Citation Information

Patent Citations

  • Nano / polymer compound modified asphalt material and preparation method thereof

    CN104559263A

  • Odor-free high-viscosity asphalt composition for water permeable pavement and preparation method of asphalt composition

    CN108395718A

  • Asphalt composition

    JP1992008766A